Premature renal epithelial cell senescence promoted by LXN/Rps3/p53 signaling pathway activation increases calcium oxalate crystal deposition by altering macrophage polarization - Chu, Maolin; Jiang, Suna; Xue, Jiawei; Li, Wenjing; Jing, Guanhua; Li, Hongying; Zhang, Juan; Xu, Wanhai (Frontiers in Immunology, 2025)
IntroductionPremature senescence of renal tubular epithelial cells (RTECs) can be caused by oxidative stress related to calcium oxalate (CaOx) kidney stones (KSs), but the role and mechanisms of cellular senescence of RTECs in the pathogenesis of kidney stones have not been fully determined. Macrophages, the most prevalent leucocyte found in nephrolithiasis, have been implicated in the pathogenesis of kidney stones.MethodsUsing oxalate (Ox) induction to simulate the hyperoxaluria microenvironment in vivo, fisetin was administered to human renal proximal tubular epithelial cells (HK-2 cells). The senescence of HK-2 cells was evaluated by detecting SA-β-gal staining, expression of senescence markers p16 and p53, and levels of senescence-associated secretory phenotype (SASP) molecules. THP-1 cells were differentiated into macrophages (M0-MΦs) using PMA induction, and macrophages in different polarization states (M1-like phenotype, M2-like phenotype) were treated with the supernatant from HK-2 cell culture. siRNA gene knockdown technology was applied to evaluate the activity of the LXN/Rps3/p53 pathway during oxalate-induced senescence in HK-2 cells. A rat model of calcium oxalate crystal-induced kidney injury was established, and the rats were divided into following groups: PBS, oxalate, oxalate + fisetin, oxalate + transfection with LXN-knockdown adeno-associated virus (AAV-shLXN), and oxalate + fisetin + AAV-shLXN, Histological assessment was performed using HE staining and Von Kossa staining of kidney tissues. The expression levels of LXN, Rps3, p53, iNOS, and CD163 in renal tissues were evaluated by immunohistochemical staining.ResultsThe onset of RTEC senescence was increased after treatment with oxalate, and the increase in RTEC senescence was reduced by fisetin treatment. Interestingly, the changes in proinflammatory M1-like phenotype polarization induced by culture medium from HK-2 cells treated with Ox+/-fisetin were consistent with the proportion of senescent HK-2 cells cultured. Furthermore, reducing cellular LXN/Rps3/p53 signaling significantly decreased SASP factors in the culture medium and simultaneously abolished M1-like phenotype macrophage polarization. More importantly, silencing renal LXN reduced RTEC senescence and M1-like phenotype macrophage polarization and consequently decreased intrarenal CaOx crystal deposition in a rat kidney stone model.DiscussionOur results demonstrate that kidney macrophage phenotype changes are related, at least in part, to RTEC senescence, and a strategy to modulate the cellular senescence of RTECs is promising as a new target for immunotherapy to treat nephrolithiasis and other age-related diseases.